Physiotherapy Intervention in Improving The Quality of Life of Scoliosis Individuals: Case Study - Naufal, Adnan Faris; Hastuti, Nimah (Universitas Muhammadiyah Surakarta, 2023)
Background: Scoliosis is a spinal problem. If scoliosis is not corrected immediately, the curvature will get worse, which can cause discomfort, an asymmetrical body appearance, and obvious changes in posture. This can also cause the quality of life to decrease. One of the public health services, namely physiotherapy, can help restore body posture by reducing the curve of the spine. Objective: To determine the quality of life of individuals with scoliosis before and after physiotherapy intervention. Method: This research design uses a case study and analytical descriptive qualitative research type. The sampling technique used is a purposive sampling technique where the inclusion and exclusion criteria have been determined and are by the research objectives. After grouping respondents, the next step was a pre-test, physiotherapy intervention and then evaluation. Results: There was an improvement in the quality of life in scoliosis patients after providing physiotherapy intervention.